Il margine che sta al centro - Giuseppe Caridi (Scienze del Territorio, 2021)
The paper develops a critical reading of the process of splitting of mountain and hill towns (mother centres) and formation of related coastal towns (marinas) along the southern Ionian side of Calabria. This process, not limited to southern Italy, is typical of the Mediterranean basin. However, in the context of study, it has assumed a general character, to the point that almost all of the mountain or hill towns have generated their own satellite centre along the coast. The author traces, from the time of Italian Unity, this turnaround in planning and evolutionary scenarios of the area, with the aim of proposing, in schematic form, the succession of the different temporal configurations, identifying the diverse thematic variables that, in various and specific ways, have affected this process. To be more precise, we witness the strategic replacement of a form of territoriality with another, more functional to the capitalist industrialisation system emerged in Italy at the end of the nineteenth century and continued throughout the post-second world war period. Such a reading, framing the process of formation of marinas within the scope of what Soja (2000) defined as the third urban revolution, is certainly of theoretical interest but has also important implications with regards to planning, in relation to which it would be useful to continue and strengthen the debate underway.